Dari Ilmu Ke Tindakan: Literasi Keuangan, Pengetahuan, Dan Kontrol Diri Dalam Pengelolaan Finansial Mahasiswa - Robby Alexander Chandra; Ickhsanto Wahyudi (Journal of Management and Creative Business, 2025)
Intelligence in dealing with life is obtained through education, parenting, and experience. Students need to understandfinancial manajement which is influenced byfinancial literacy "FL ", financial knowledge "FK ", self-control "KD" (locus of control), and (financial behavior "FB ''). This study examines the relationship of thesefactors in student financial manajement, especially at Esa Unggul University. Further research is needed to understand their impact in order to increase financial awareness among students. This study uses a quantitative approach with the variables FL, FK, and KD as independent, and FB as dependent. Data was collected through an online questionnaire and analyzed using PLS-SEM (partial least squares structural equation modeling). Validityand reliability tests were conducted with a pre-test to ensure the research model was valid and reliable. From the total 167 respondents, 20 leaving, others 147students participating to .fill quesioer. Model evaluation shows that all constructs meet validity and reliability.KD has the greatest influence on FB with a value of 0.4 74, followed by FK with 0. 24 7, while FL is not significant with a value of 0. 056. Hypothesis testing shows that only FK and KD have a significant effect on FB, while FL does not make a significant contribution. The practical implication is that focusing on financial knowledge and self-control improves students' financial behavior. Further research needs to explorefactors and methodologies.